A new Al80Mg10Si5Cu5 multicomponent aluminium alloy: Microstructure, mechanical, and physical properties - Ester Villanueva; Iban Vicario; Ignacio Crespo; Teresa Guraya; Iñaki Hurtado; Joseba Albizuri (Journal of Materials Research and Technology)
This study investigates the microstructure, mechanical, and physical properties of a newly developed and patented multicomponent aluminium alloy based on the AlMgSiCu system, produced by High Pressure Die casting (HPDC). This alloy exhibits superior mechanical properties compared to other HPDC alloys, especially at elevated temperatures. Tested at both room temperature (RT), and at 200 °C, a range where most aluminium alloys degrade, it demonstrated remarkable thermal stability, maintaining its characteristics. The alloy's complex microstructure includes an aluminium matrix with Mg2Si, Al2Cu, and Al2CuMg phases. At 200 °C, the alloy's hardness was twice that of the commonly used AlSi9Cu3 alloy. The yield strength (YS) reached 244 MPa, ultimate tensile strength (UTS) 267 MPa, and elongation (E) of 0.69 %, showing a 65 % increase in YS and a 45 % increase in UTS, compared to AlSi9Cu3 alloy. In compressive testing, the alloy also showed superior results, with a YS of 251 MPa, ultimate compressive strength (UCS) of 468 MPa, and deformation (D) of 18.50 %, with a 90 % increase in YS and an 80 % increase in UCS. The results are significant, despite a 40 % lower deformation compared to AlSi9Cu3. The transformation of the Al2Cu phase with temperature to form the Al2CuMg phase had a significant impact on the material's overall mechanical properties, maintaining the mechanical properties at 200 °C. Comparing the YS, UTS and UCS-to-density ratio at 200 °C, this alloy shows great potential for high-temperature applications being an attractive candidate for aerospace and automotive sectors, particularly for components like drum brakes, traditionally made of cast iron.